1984
DOI: 10.1002/hep.1840040318
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nutrition on Unconjugated Plasma Bilirubin Concentrations in Squirrel Monkeys†

Abstract: Bolivian squirrel monkeys (Saimiri sciureus) have fasting unconjugated hyperbilirubinemia (males: 2.0 +/- 0.14; females: 3.0 +/- 0.26 mg per dl) which resembles that of humans with Gilbert's syndrome. Closely related Brazilian squirrel monkeys have fasting levels (males: 0.29 +/- 0.045; females: 0.36 +/- 0.073 mg per dl) similar to normal people. The purpose of this study was to identify the underlying mechanisms and the nutritional factors involved. Both Bolivian and Brazilian squirrel monkeys had higher plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…It was reported that nutrition and fasting affected the plasma bilirubin concentration in squirrel monkeys. 16 Creatinine was higher in males compared to females similar to previous studies. 2,7,8 The observed sex-related difference in creatinine could be due to relatively higher muscle mass in males as previously described.…”
Section: Discussionsupporting
confidence: 90%
“…It was reported that nutrition and fasting affected the plasma bilirubin concentration in squirrel monkeys. 16 Creatinine was higher in males compared to females similar to previous studies. 2,7,8 The observed sex-related difference in creatinine could be due to relatively higher muscle mass in males as previously described.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, these results suggest that exogenous glucose may increase the availability of uridine diphospho (UDP)-glucuronate for the hepatic conjugation of bilirubin in fasting subjects. 26 The reasons for the discrepancies between Portman's results dial ours are uncertain, but may be explained by differences in the composition of the food (calorie intake), in duration of feeding, and species differences.…”
Section: Reduced Caloric Intake and Diet Testsmentioning
confidence: 67%
“…On the other hand, Portman et al 26 reported that carbohydrates lowered fasting hyperbilirubinemia and increased bilirubin excretion in bile in Bolivian squirrel monkeys. Furthermore, these results suggest that exogenous glucose may increase the availability of uridine diphospho (UDP)-glucuronate for the hepatic conjugation of bilirubin in fasting subjects.…”
Section: Reduced Caloric Intake and Diet Testsmentioning
confidence: 97%
“…Fasting hyperbilirubinemia is rapidly reversed by oral or intravenous administration of carbohydrates, but not by lipid administration. 354 …”
Section: Animal Modelmentioning
confidence: 97%